2005
DOI: 10.1186/1471-2334-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Defining the timing of respiratory syncytial virus (RSV) outbreaks: an epidemiological study

Abstract: Background: Seasonal RSV infections occur every year and affect particularly children under six months of age. Passive immunoprophylaxis with monoclonal antibody Palivizumab is recommended in the period with high risk of RSV infection. This study aims to define the period for the southern part of Germany (Stuttgart area).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
44
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 18 publications
11
44
0
3
Order By: Relevance
“…RT-PCR detected RSV in 41.2% of our infants. RSV bronchiolitis followed the typical seasonal pattern with a peak incidence during the winter months (February 2005, February 2006 and December 2006) 21 22. After RSV, the other viruses most frequently detected among infants with acute bronchiolitis in our study were hBoV and RV.…”
Section: Discussionsupporting
confidence: 55%
“…RT-PCR detected RSV in 41.2% of our infants. RSV bronchiolitis followed the typical seasonal pattern with a peak incidence during the winter months (February 2005, February 2006 and December 2006) 21 22. After RSV, the other viruses most frequently detected among infants with acute bronchiolitis in our study were hBoV and RV.…”
Section: Discussionsupporting
confidence: 55%
“…Other European countries, such as Switzerland, Sweden, and Finland, observed a yearly varying pattern of early and late seasons, whereas early seasons are associated with high incidences and vice versa (10,41,53). Previous reports from Germany including regions around Kiel, Stuttgart, and Freiburg also described a biennial rhythm of severe early and weak late seasons (3,50,58). An explanation for the absence of the biennial pattern in our study might be due to missed cases Apart from that, we observed no frequency in severe or weak RSV seasons as described previously.…”
Section: Discussionmentioning
confidence: 93%
“…We speculate that the decrease in hospitalization rates observed in the registry may reflect year-to-year variability in RSV epidemiology across seasons and geographic regions. 28,29 Other potential sources of variation were changes in participating sites, physicians, and study populations, and disparity in hospital admission criteria and RSV testing practices over the four consecutive seasons. In the registry, the number of hospitalizations was not based on direct review of hospital discharge records, but rather on chart review in pediatricians' offices and ongoing contact with patient caretakers during the study period.…”
Section: Discussionmentioning
confidence: 99%